2014
DOI: 10.1186/2008-2231-22-22
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, analgesic and anti-inflammatory activities of new methyl-imidazolyl-1,3,4-oxadiazoles and 1,2,4-triazoles

Abstract: BackgroundLong-term clinical employment of nonsteroidal anti-inflammatory drugs (NSAIDs) is associated with significant side effects including gastrointestinal (GI) lesions and kidney toxicity. In this paper we designed and synthesized new imidazolyl-1,3,4-oxadiazoles and 1,2,4-triazoles by molecular hybridization of previously described anti-inflammatory compounds in the hope of obtaining new safer analgesic and anti-inflammatory agents.MethodsThe target structures were synthesized by preparation of 5-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Fragment-based parameters of drug likeness and drug score were evaluated using Osiris Property Explorer version 2.0 49 as previously described. 50 Analysis from Osiris Property Explorer software revealed that all 4,5-dihydro-1H-imidazolyl pyrazoles derivatives (5a-g) presented a better fragmentbased drug likeness profile in comparison with the pyrazolyl-1H-tetrazole substituted analogs (Figure 9a), suggesting the improved pharmacophoric profile of 4,5-dihydro-1H-imidazolyl pyrazoles rings in comparison with analogs tetrazoles. The combined analysis of druglikeness, aqueous solubility (clog S), partition coefficient of n-octanol/water (clog P) and molecular weight values corroborates to such profile revealing better overall drug score values for the 5a-g series in comparison with the 1a-g series (Figure 9b).…”
Section: Lead Likeness Parameters and In Silico Toxicology Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragment-based parameters of drug likeness and drug score were evaluated using Osiris Property Explorer version 2.0 49 as previously described. 50 Analysis from Osiris Property Explorer software revealed that all 4,5-dihydro-1H-imidazolyl pyrazoles derivatives (5a-g) presented a better fragmentbased drug likeness profile in comparison with the pyrazolyl-1H-tetrazole substituted analogs (Figure 9a), suggesting the improved pharmacophoric profile of 4,5-dihydro-1H-imidazolyl pyrazoles rings in comparison with analogs tetrazoles. The combined analysis of druglikeness, aqueous solubility (clog S), partition coefficient of n-octanol/water (clog P) and molecular weight values corroborates to such profile revealing better overall drug score values for the 5a-g series in comparison with the 1a-g series (Figure 9b).…”
Section: Lead Likeness Parameters and In Silico Toxicology Predictionmentioning
confidence: 99%
“…Apixaban and argatroban were used as controls for FXa and thrombin, respectively. Experimental IC 50 values were based on a substrate concentration of 250 µM and were obtained by fitting a normalized response of FXa catalytic activity vs. inhibitor concentration to nonlinear regression models using Matlab. 70 Ki values of the inhibitory molecules were determined by fitting the initial velocity vs. substrate concentration data to nonlinear regression models using the GraphPad Prism software, 71 The Ki values are expressed as final assay concentrations.…”
Section: Enzymes Chromogenic Activitymentioning
confidence: 99%
“…1,3,4‐Oxadiazoles are valuable five‐membered aromatic heterocycles that possess a wide range of biological properties, including antibacterial, antifungal, antiviral, anti‐inflammatory, antiparasitic, and anti‐HIV activities. Some examples of drugs used in clinical medicine, containing the 1,3,4‐oxadiazole unit, are furamizole, which is an antibiotic drug, and raltegravir, an antiretroviral medication used to treat HIV infection (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…9 It was reported that triazole compounds exhibited kinds of pharmacological abilities, such as anti-inflammatory, analgesic, antinociceptive, antiepileptic etc. [10][11][12][13][14][15][16] 1,2,3-Triazole and 1,2,4-triazole all possess anti-inflammatory activity. [11][12][13]16 In order to search new compounds with higher anti-inflammatory activities and lower toxicity, 1,2,3-triazole and 1,2,4-triazole derivatives were designed on the basis of association principle.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] 1,2,3-Triazole and 1,2,4-triazole all possess anti-inflammatory activity. [11][12][13]16 In order to search new compounds with higher anti-inflammatory activities and lower toxicity, 1,2,3-triazole and 1,2,4-triazole derivatives were designed on the basis of association principle. All of these 5-(1-Benzyl-1H- [1,2,3]triazol-4-yl)-4-phenyl-4H- [1,2,4] triazole-3-thiol derivatives were synthesized, and then the anti-inflammatory activities (in vitro) were evaluated.…”
Section: Introductionmentioning
confidence: 99%